Análisis de los efectos ambientales, provocados por los aceites provenientes de las lubricadoras de la ciudad de Zamora, cantón Zamora - Jumbo Alejandro, José Geovany (2015)
The purpose of the present research is to Analyze the environmental effects caused by oils from lubricators and car washes in Zamora city of Zamora County. First, it was made a preliminary diagnosis and characterization of the processes and activities of each establishments under study. The results led to the conclusion that the parameter with major anomalies are oils and fats, which discharge limits to the sewage contained in Table No 11 of Book VI of TULSMA is evident, as well as discharge limits to freshwater bodies contained in Table No 12, which exceed the maximum allowable limit. Finally, a guide to good environmental practices that are contained in the plans and measures that will allow the reduction of the pollution load in the wastewater is proposed